Communication Systems of Smart Agriculture Based on Wireless Sensor Networks in IoT - Atmaja, Ardian Prima; Hakim, Aulia El; Wibowo, Ari Purnomo Aji; Pratama, Lasardi Abdi (Journal of Robotics and Control (JRC), 2021)
As technology develops, major countries have begun to implement the Smart Agriculture system and Internet of Things to facilitate farmers in managing their agricultural land. This study discusses the communication system of Smart Agriculture based on Internet of Things. Data from the sensor will be sent by Wireless Sensor Network to Raspberry Pi and send it to the database server which can then be accessed via the internet using android applications. Android applications can be used to monitor soil pH sensors and moisture. In addition, the control of sluice gates and water pumps can also be done manually and automatically. So that water can be controlled through applications and the web remotely. The success percentage of the communication system of Smart Agriculture based on the Internet of Things is 100% because all data from the sensor are successfully received by the Raspberry Pi and sent to the database so it can be accessed through the built-in android application and website.